1998 IEEE Ultrasonics Symposium. Proceedings (Cat. No. 98CH36102)
DOI: 10.1109/ultsym.1998.762265
|View full text |Cite
|
Sign up to set email alerts
|

Arrayed-coil EMAT for longitudinal wave in steel wires

Abstract: Two types of electromagnetic acoustic transducers (EMATs) with arrayed coils are developed for longitudinal wave in steel wires. One amplifies the signal by overlapping the pulses from all coils in phase. The other cancels one of two directional waves, propagated symmetrically in the wire, by overlapping two antiphase waves. Combination of these two types of the EMATs enables us to launch the longitudinal wave of sufficient amplitude in one direction, which can be used in long-ranged flaw detection in steel wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The directivity pattern of the fabricated EMATs were also experimentally evaluated as shown in Fig. 6 of ref [50] by the authors; techniques have been reported to suppress the unwanted direction [51], but in this work, we used two EMAT receivers to identify forward and backward travelling waves. This bidirectional characteristic of the waves generated by PPM-SH EMATs makes it difficult to interpret which side of the sample is the source of the resulting echo; however, this information is needed for OGM in addition to the range.…”
Section: Range and Direction Estimationmentioning
confidence: 99%
“…The directivity pattern of the fabricated EMATs were also experimentally evaluated as shown in Fig. 6 of ref [50] by the authors; techniques have been reported to suppress the unwanted direction [51], but in this work, we used two EMAT receivers to identify forward and backward travelling waves. This bidirectional characteristic of the waves generated by PPM-SH EMATs makes it difficult to interpret which side of the sample is the source of the resulting echo; however, this information is needed for OGM in addition to the range.…”
Section: Range and Direction Estimationmentioning
confidence: 99%
“…Numerical solvers have been developed to calculate dispersion characteristics [17,18] and the theory has been adapted to model the effects of bends, defects and supports [19][20][21][22]. Piezoelectric, magnetostrictive and electromagnetic transducers (EMATs) have been developed for different pipe materials [23][24][25][26][27][28] and include unidirectional and modeselecting types [29,30]. Apart from the T (0, 1) mode [31], guided acoustic modes are dispersive, and reflection and mode conversion occur at discontinuities.…”
Section: Introductionmentioning
confidence: 99%